Analysis of fluid flow (fully developed flow) in a circular Pipe by using fluent CFD - wildan fathoni (Universitas Sultan Ageng Tirtayasa, 2018)
Basically the fluid flow in a circular pipe undergoing development value of speed. To find out the value of a point of commencement the development speed of flow in the pipe can be known with the help of software CFD FLUENT computational equation model with k-epsilon turbulence flow for high value Reynold, later CFD simulation results will be compared with the results of the calculations manually. In this simulation aims to perform a simulation on turbulent flow modeling in the pipe and to know the point of the beginning fully developed of the fluid flow in the pipe. Variations of the model has a tested pipe diameter size 0.0254 m and 0.0508 m length each pipes every 2 meters. The incoming fluid flow velocity 1 m/s on each pipe obtained results with the highest flow rate value on the pipe diameter 0.0254 m of 1,241 m/s, and the value of the pressure of 972 Pa, while in 0.0508 m diameter pipe of 1,233 m/s, pressure value 427 Pa. The start of the fully developed simulations on a pipe diameter 0.0254 m in length to 0.55 m, and the diameter of the pipe to 0.0508 m in length to 1.2 m. Diameter pipe on simulation results 0.0508 m closer to the results using equations from the book (Munson, 2010) and equations (Bhatti & Shah) with a difference of 0.16 m, pipe diameter to 0.0254 m simulation results closer to equations from the book (Munson, 2010) by difference of 0.05 m. Pipe diameter size effect on the value of a fully developed, the larger diameter of the pipe is then fully developed his values will increasingly long.